Wage compression and the gender pay gap - Lawrence M. Kahn (IZA World of Labor, 2015)
There are large international differences in the gender pay gap. In some developed countries in 2010–2012, women were close to earnings parity with men, while in others large gaps remained. Since women and men have different average levels of education and experience and commonly work in different industries and occupations, multiple factors can influence the gender pay gap. Among them are skill supply and demand, unions, and minimum wages, which influence the economywide wage returns to education, experience, and occupational wage differentials. Systems of wage compression narrow the gender pay gap but may also lower demand for female workers.
Keywords: J31; J16; J50; 330; gender; wage inequality; collective bargaining; minimum wages; unions